Study on underground storage of potato (Solanum tuberosum) during winter in Ladakh (Current Horticulture, 2024)
The passive underground storage of potato  (Solanum tuberosum) was designed and potato  tubers of Kufri Jyoti, Kufri Himalini and Kufri  Girdhari were stored in passive underground storage  during November 2022 - April 2023 at Defense Institute  of High-Altitude Research, Leh Ladakh. Of three  cultivars, tubers of Kufri Girdhari showed lowest total  weight loss as compared to other varieties. Potato is most valued non cereal crop in Ladakh. It  is consumed by the locals as well as the army deployed  here, all through the season. The crop is multiplied  vegetatively using tuber as seed material usually (Paul  et.al., 2022). The crop is cultivated in May and harvested  in September. During the harsh cold winter, continuous  supply of fresh vegetables is not possible as the region  remains landlocked during November - May. Transport  of vegetables through air route is expensive as it charges  around Rs 130/kg. In such cases, storage of potato for  long period of winter becomes essential (Singh and  Srivastava ,2012). Moreover, to address food insecurity,  it is crucial to boost productivity and expand the area  dedicated to potato production (Jatav et.al., 2023) The study was carried out in underground passive  storage located at Leh (77.57298º E; 34.13298º N;  elevation 11482 ft) during November - April (Fig 1).  Potato tubers of Kufri Jyoti, Kufri Himalini and Kufri  Girdhari were used for study. Potatoes were properly  cured, free from damages and stored in perforated leno  bags (35kg each). The observation for weight loss and  rotting were done monthly. Temperature and humidity  were also recorded during the storage period with testo  175 H1 data logger.
Keywords: vegetables; Girdhari; Ladakh